2018
DOI: 10.1111/jpi.12480
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and density of melatonin receptors in human main pancreatic islet cell types

Abstract: Recent investigations of our group established that melatonin modulates hormone secretion of pancreatic islets via melatonin receptor types MT1 and MT2. Expression of MT1 and MT2 has been shown in mouse, rat, and human pancreatic islets as well as in the β-, α-, and δ-cell lines INS-1, αTC1.9, and QGP-1. In view of these earlier investigations, this study was performed to analyze in detail the distribution and density of melatonin receptors on the main islet cell types in human pancreatic tissue obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 77 publications
0
17
0
3
Order By: Relevance
“…It is believed that the decreased glucose level in diabetic rat models is attributed to the restoration of pancreatic islet cells by ML [ 71 ]. Melatonin receptors are found in many cells, including pancreatic β-cells and cardiomyocytes, indicating the prevalent effects of MLT on several physiological functions [ 25 ]. It was reported that MLT protects pancreatic β-cells from STZ-induced cellular oxidative injury and the development of T2DM [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that the decreased glucose level in diabetic rat models is attributed to the restoration of pancreatic islet cells by ML [ 71 ]. Melatonin receptors are found in many cells, including pancreatic β-cells and cardiomyocytes, indicating the prevalent effects of MLT on several physiological functions [ 25 ]. It was reported that MLT protects pancreatic β-cells from STZ-induced cellular oxidative injury and the development of T2DM [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the melatonin treated group (MLT), rats were given MLT (10 mg/kg) by stomach tube daily for 15 days between 10:0 and 11:00 am [ 28 ]. The 3 rd group was diabetic group (DM) in which the rats were treated with single dose of nicotinamide following STZ [ 25 ] to develop diabetes. In the fourth group, rats were injected with MLT at 3 rd day after induction of diabetes for 15 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, GWAS have shown that the rs10830963 risk variant of MTNR1B, which confers increased expression of the receptor in human pancreatic islets [15], is associated with impaired fasting glucose, measures of decreased insulin secretion and increased T2D risk [15][16][17][18][19][20]. Furthermore, in vitro, melatonin administration stimulates secretion of somatostatin-an insulin-inhibitory hormone-in human pancreatic islets [21,22]. Also, placebo-controlled human experimental studies have demonstrated that acute melatonin administration worsens glucose tolerance, both in aged women [23] and in young women [24], and both in the morning and in the evening [24].…”
Section: Is Melatonin Deleterious For T2d?mentioning
confidence: 99%
“…Melatonin acts as a synchronizing agent (zeitgeber) on the islets’ circadian oscillator, inducing a shift in the rhythm of insulin secretion [ 5 , 6 , 12 , 13 ]. The mechanisms of melatonin action on β-cells differ between animals [ 5 , 12 , 13 , 14 ]. In the rat, melatonin negatively affects insulin secretion both in vitro and in vivo [ 5 , 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%